Haiti : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2001 Article IV Consultation highlights that Haiti's performance under the Staff-Monitored Program (SMP) during FY2000/01 was weak. Real GDP is estimated to have declined by about 2 percent, reflecting tight monetary conditions and the negative expectations raised by the continuing high fiscal imbalance and central bank financing; inflation remained broadly unchanged at about 16 percent during most of the year. Tight monetary conditions and crowding out by the public sector combined with the weak economy and continuing political uncertainty all contributed to a sharp decline in credit to the private sector.